The pre‐seventh pandemic Vibrio cholerae BX 330286 El Tor genome: evidence for the environment as a genome reservoir - Haley, Bradd J.; Grim, Christopher J.; Hasan, Nur A.; Taviani, Elisa; Jongsik, Chun; Brettin, Thomas S.; Bruce, David C.; Challacombe, Jean F.; Detter, J. Chris; Han, Cliff S.; Huq, Anwar; Nair, G. Balakrish; et al. (Environmental Microbiology ReportsEnvironmental Microbiology Reports, 2010)
Vibrio cholerae O1 El Tor BX 330286 was isolated from a water sample in Australia in 1986, 9 years after an indigenous outbreak of cholera occurred in that region. This environmental strain encodes virulence factors highly similar to those of clinical strains, suggesting an ability to cause disease in humans. We demonstrate its high similarity in gene content and genome-wide nucleotide sequence to clinical V. cholerae strains, notably to pre-seventh pandemic O1 El Tor strains isolated in 1910 (V. cholerae NCTC 8457) and 1937 (V. cholerae MAK 757), as well as seventh pandemic strains isolated after 1960 globally. Here we demonstrate that this strain represents a transitory clone with shared characteristics between pre-seventh and seventh pandemic strains of V. cholerae. Interestingly, this strain was isolated 25 years after the beginning of the seventh pandemic, suggesting the environment as a genome reservoir in areas where cholera does not occur in sporadic, endemic or epidemic form.